Borders of a lip : Romanticism, language, history, politics - Plug, Jan. (Albany : State University of New York Press, 2003)
Explores the role of language, history, and politics in Romantic literature and thought, from Kant to Yeats.
pt. 1. The sign of history: Kant and Lyotard, Wordsworth. "As if" history--Kant, then and now. Naming history: Wordsworth -- pt. 2. Bordering the political: Kleist. Legal matter: Der zerbrochne Krug. Borders, crossing: Die Hermannsschlacht -- pt. 3. The debts of history: Shelley and Yeats. Crossing culture: The last man. A specular nation: Yeats's myth of the Irish -- Threats, responses: an afterword.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Romanticism -- Europe; European literature -- 19th century -- History and criticism; Romantisme -- Europe; Littérature européenne -- 19e siècle -- Histoire et critique; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; European literature; Romanticism; Europe; 1800-1899; Criticism, interpretation, etc